The protective effect of fish oil against cisplatin induced eye damage in rats - Baykalir, Burcu Gul; Ciftci, Osman; Cetin, Asli; Turkmen, Nese Basak (Taylor & Francis Ltd, 2018)
Ocular toxicity induced by anticancer chemotherapy is not uncommon, but underestimated and under-reported. Visual changes have been attributed to a number of chemotherapeutic agents in humans. Cisplatin (CP), a heavy metal compound, is used in the treatment of many types of tumours. CP is known to produce nonspecific blurred vision, papilledema, and optic neuritis for high doses as well as cumulative dose regimens. The aim of this study was to investigate the possible beneficial effects of fish oil (FO) on eye tissue oxidative status and histological alterations against CP-induced in the rats. The animals were randomly divided into the following four groups: the control, CP, FO, and CP+FO groups. CP was intraperitoneally administered at the dose of 7mg/kg and FO was orally given at 1 softgel per day for 14days. The eye injury was assessed by biochemical and histological examinations. The levels of thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH), activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were evaluated in the eye tissue. TBARS levels were significantly higher, the activities of the antioxidant enzyme and GSH levels were significantly lower in the CP group than in the control group. The histopathological evaluation also confirmed the foregoing findings. On the other hand, treatment of FO ameliorated the biochemical and histological alterations caused by CP. The results showed that treatment with FO may protect against the negative ocular effects of CP.
Keywords: Cisplatin; fish oil; eye; oxidative stress; rat